Demonstration of an optical phase conjugation based dual‐hop PDM‐QPSK free‐space optical communication link. Issue 6 (7th January 2022) - Chen, Junfan; Yu, Zhaoxin; Wang, Tianshu; Liu, Zhi; Gao, Shiming
Abstract: The dual‐hop free‐space optical (FSO) communication link for polarization‐division multiplexing quadrature phase‐shift keying (PDM‐QPSK) signals is proposed and experimentally demonstrated in an atmospheric chamber with the optical phase conjugation (OPC) compensating the turbulence‐induced signal distortions. The phase fluctuations can be effectively reduced by the OPC, as the error vector magnitudes are 10.03% and 8.28% decreased for x‐ and y‐ polarization. At the bit error rate of 1 × 10 –3, the power penalty of the dual‐hop link with OPC is 2.85 or 2.34 dB lower than that of each polarization without OPC.